The impact of a plant-based diet on the menstrual cycle and female fertility - Karina Ekiert; Katarzyna Pilarczyk; Aleksandra Rabęda; Natalia Klepacz; Zuzanna Cudziło; Hubert Sawczuk; Weronika Ewa Nowak; Marta Kaus; Hanna Adamska; Marta Malicka (Journal of Education, Health and Sport)
Introduction and objective: A plant-based diet is being adopted by an increasing number of people worldwide. Its health benefits have been described in numerous scientific studies. Unfortunately, an improperly balanced diet that excludes animal-derived products can, through various mechanisms, lead to deficiencies and disruptions in the functioning of many systems in the body. This review paper aims to present and summarize the findings and current literature on the impact of a plant-based diet on the menstrual cycle and female fertility.